Benefits of Maternal Thiamine Supplementation for Enhancing Cambodian Infants’ Social Responsiveness at 24 Weeks - Baldwin, Dare A (Curr Dev Nutr, 2021)
OBJECTIVES: Infants in Cambodia are at risk for thiamine deficiency, with long-term negative consequences for neuro-cognitive development. We investigated the extent to which maternal thiamine supplementation enhances infants’ responsiveness to social engagement. Such responsiveness is both indicative of neuro-cognitive development and beneficial for subsequent neuro-cognitive progress. METHODS: 335 lactating Cambodian mothers were randomly assigned to receive a capsule containing 0, 1.2, 2.4, or 10 mg of thiamine daily from 2- until 24-weeks postnatal. We assessed infants’ social responsiveness via a new method – the Primary Engagement Task (PET) – when infants were 2-, 12-, and 24-weeks. In the PET, mothers were asked to elicit and sustain a smile from infants as they added and then removed modalities of engagement (eye-contact/facial expression, voice and touch) across six 30-second “epochs.” Subsequent behavioral coding from video-recordings determined changes in infants’ state across the epochs of the PET. RESULTS: Preliminary analyses based on 103 of the 335 infants in the PET at 24 weeks revealed that infants displayed significantly increased alertness as mothers introduced new modalities of engagement in the PET, and a partial decline in alertness as modalities were removed (linear contrast F(1,102) = 24.37, P = 0.000; quadratic contrast F(1,102) = 7.27, P = 0.008). Although maternal thiamine dosage did not influence these patterns overall (F's < 1.56, P's > 0.20), higher maternal thiamine dosage was associated with infants displaying enhanced alertness when mothers first offered eye-contact in the PET (beta-weight = 0.026; t = 2.01, P = 0.047). This pattern of alerting to maternal eye-contact was statistically significant only in the 10 mg group (paired t(25) = 3.14, P = 0.004). CONCLUSIONS: Infants whose mothers received 10 mg daily thiamine supplementation displayed increased alertness to opportunities to interact socially. These preliminary findings (a) showcase the value of the PET for assessing infants’ responsiveness to caregiver's efforts to engage them socially, and (b) hint that maternal thiamine supplementation promotes infants’ social responsiveness, thereby underscoring the importance of infants’ early access to adequate thiamine for neuro-cognitive thriving. FUNDING SOURCES: Bill & Melinda Gates Foundation & New York Academy of Sciences.